Emodin enhances antitumor effect of paclitaxel on human non-small-cell lung cancer cells in vitro and in vivo - Chen S; Zhang Z; Zhang J (Dove Medical Press, 2019)
Shuifang Chen, Zeying Zhang, Jianli ZhangDepartment of Respiratory Medicine, The First Affiliated Hospital, College of Medicine, Zhejiang University, Hangzhou, Zhejiang 310003, People’s Republic of ChinaBackground: Non-small-cell lung cancer (NSCLC) was known as the most malignant tumor. Paclitaxel (PTX) is the effective drug used for the treatment of NSCLC; however, it also exhibits severe side effects. Emodin could induce apoptosis of NSCLC cells and serve as a potential cancer therapeutic agent. However, the effects of combination of emodin with PTX on NSCLC remain unclear. Thus, this study aimed to investigate the effects of emodin in combination with PTX on A549 cells.Materials and methods: The effects of combination treatment on the proliferation, apoptosis and invasion of NSCLC cells were evaluated by CCK-8, flow cytometric and TUNEL assays, respectively. In addition, Western blotting was used to detect the expressions of Bax, Bcl-2, active caspase 3, p-Akt and ERK in cells.Results: Combination of emodin with PTX synergistically inhibited the proliferation of A549 cells in vitro. In addition, we found that emodin significantly enhanced PTX-induced apoptosis in A549 cells via increasing the expressions of Bax and active caspase 3 and decreasing the levels of Bcl-2, p-Akt and p-ERK. Moreover, emodin markedly enhanced antitumor effect of PTX on A549 xenograft without significant side effects in vivo.Conclusion: Our findings indicated that emodin could significantly enhance antitumor effect of PTX in vitro and in vivo. Therefore, the combination of emodin with PTX may serve as a potential strategy for the treatment of patients with NSCLC.Keywords: non-small-cell lung cancer, emodin, paclitaxel, apoptosis